Post forest-fire hydrochemical behaviour of the Rimbaud catchment (Massif des Maures, France) (ZEITSCHRIFT FUR GEOMORPHOLOGIE, 1999)
In August 1990, a forest fire devastated 84 % of the Rimbaud catchment area (1.46 km(2)). This catchment presents a substratum composed of gneiss. Its relief is sharp. Soils are skeletal. The forest fire destroyed a maquis (with treelike heather and arbustus) interspersed with cork oaks and maritime pines. The fire's effects on the chemical composition of the runoff have remained light in terms of low flows. On the other hand, mineralization has greatly increased during flood, especially at the beginning of the 1990-91 water year. The paper reports on the observations conducted during four years after the fire. Dissolved outputs and hydrochemical balances are compared with results obtained on the same catchment before the forest fire, and on the Boussicaut catchment (0.74 km(2)), which is very close by, but which was not burnt.
APS